Best Practices to Maximize the Use and Reuse of Quantitative and Systems Pharmacology Models: Recommendations From the United Kingdom Quantitative and Systems Pharmacology Network. (22nd March 2019) - Cucurull‐Sanchez, Lourdes; Chappell, Michael J.; Chelliah, Vijayalakshmi; Amy Cheung, S. Y.; Derks, Gianne; Penney, Mark; Phipps, Alex; Malik‐Sheriff, Rahuman S.; Timmis, Jon; Tindall, Marcus J.; van der Graaf, Piet H.; Vicini, Paolo; et al.
Abstract : The lack of standardization in the way that quantitative and systems pharmacology (QSP) models are developed, tested, and documented hinders their reproducibility, reusability, and expansion or reduction to alternative contexts. This in turn undermines the potential impact of QSP in academic, industrial, and regulatory frameworks. This article presents a minimum set of recommendations from the UK Quantitative and Systems Pharmacology Network (UK QSP Network) to guide QSP practitioners seeking to maximize their impact, and stakeholders considering the use of QSP models in their environment.